OPTIMALISASI PRODUKSI IKAN LELE ASAP DENGAN OTOMATISASI ATMEGA 8 - Arry Darmawan; Doni Bowo Nugroho (Institut Sains dan Teknologi Nasional, 2021)
The purpose of this study was to design and determine the ability of the catfish smoking system automatically using the ATMega8 microcontroller and the LM 35 temperature sensor as an optimization of catfish smoking production, as well as to conduct a comparative study of smoked catfish quality and economic analysis with conventional systems. The type of research used is research and development with a 4D model approach (define, design, develop and desiminate) and comparative analysis. Data obtained through observation, testing and documentation. Then analyzed qualitatively and quantitatively. The results obtained from this study are the design of a catfish smoking system automatically using an ATMega8 microcontroller and a temperature sensor as an optimization of catfish smoking production. The workings of the catfish smoking system is to control the rotation and smoking time using an ATMega8 microcontroller. The smoking system is able to produce 2 kilograms of smoked catfish in 120 minutes with a distance of 40 cm with a quality water content of 58.14%, ash content of 5.93%, pH value of 6.56 and TBA value of 0.02. Keyword: catfish, smoking, microcontroller